Tax Avoidance As Variables Moderation, Influence Profitability, Leverage, Size Of Business, And Growth Sales To Financial Distress - Khorida AR; Andry Priharta; Luqman Hakim; Indra Gunawan Siregar; Fany Yoga Pratama (UNIVED Press, 2026)
The purpose of this empirical study, which involved 199 manufacturing companies listed on the Indonesian Stock Exchange from 2018 to 2022, is to determine how profitability, leverage, company size, and sales growth influence financial distress. Tax avoidance is used as a moderating variable. A total of 154 companies were purposively sampled. Panel data regression and moderation regression analyses were used in the research process. This study used Eviews 13. The results show that financial distress is influenced by profitability, leverage, and sales growth. On the other hand, financial distress is not influenced by company size or tax avoidance. In addition, tax avoidance does not reduce the impact of profitability, leverage, company size, and sales growth on financial distress.